Class II histone deacetylases require P/Q-type Ca2+ channels and CaMKII to maintain gamma oscillations in the pedunculopontine nucleus - Urbano Suarez, Francisco Jose (2018)
Epigenetic mechanisms (i.e., histone post-translational modification and DNA methylation) play a role in regulation of gene expression. The pedunculopontine nucleus (PPN), part of the reticular activating system, manifests intrinsic gamma oscillations generated by voltage-dependent, high threshold N- and P/Q-type Ca2+ channels. We studied whether PPN intrinsic gamma oscillations are affected by inhibition of histone deacetylation. We showed that, a) acute in vitro exposure to the histone deacetylation Class I and II inhibitor trichostatin A (TSA, 1 μM) eliminated oscillations in the gamma range, but not lower frequencies, b) pre-incubation with TSA (1 μM, 90–120 min) also decreased gamma oscillations, c) Ca2+ currents (ICa) were reduced by TSA, especially on cells with P/Q-type channels, d) a HDAC Class I inhibitor MS275 (500 nM), and a Class IIb inhibitor Tubastatin A (150–500 nM), failed to affect gamma oscillations, e) MC1568, a HDAC Class IIa inhibitor (1 μM), blocked gamma oscillations, and f) the effects of both TSA and MC1568 were blunted by blockade of CaMKII with KN-93 (1 μM). These results suggest a cell type specific effect on gamma oscillations when histone deacetylation is blocked, suggesting that gamma oscillations through P/Q-type channels modulated by CaMKII may be linked to processes related to gene transcription.